DOI: 10.11606/d.55.2015.tde-14092015-164510
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de alunos em ambientes de ensino online: estendendo o uso da DAMICORE para minerar dados educacionais

Abstract: À Vanessa Kiraly, com admiração e gratidão por sua compreensão, carinho, presença e incansável apoio ao longo do período de elaboração deste trabalho.A Renata Moreira Grass por toda a sua ajuda e dedicação para a conclusão desse trabalho.Aos meus amigos que tanto me apoiaram durante essa caminhada, em especial, ao Daniel Tozadore pelos momentos de alegria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…DAMICORE requires no parameters setup to run (although some execution options may improve its performance). DAMICORE has been successfully employed in a variety of fields, for example, software-hardware co-design [16,17,18], compiler optimization [19,20], student profiling in e-learning environments [21,22], identification of phytopathology from sensor data [18], systematic literature review, identification of cross-cut concerns [23], electrical distribution systems [24], and novel methods in bioinformatics [25]. Feature Sensitivity Analysis.…”
Section: Data Mining Methodology Adopted -Fs-opamentioning
confidence: 99%
See 1 more Smart Citation
“…DAMICORE requires no parameters setup to run (although some execution options may improve its performance). DAMICORE has been successfully employed in a variety of fields, for example, software-hardware co-design [16,17,18], compiler optimization [19,20], student profiling in e-learning environments [21,22], identification of phytopathology from sensor data [18], systematic literature review, identification of cross-cut concerns [23], electrical distribution systems [24], and novel methods in bioinformatics [25]. Feature Sensitivity Analysis.…”
Section: Data Mining Methodology Adopted -Fs-opamentioning
confidence: 99%
“…The former only works on the objective space for the exclusive purpose of space reduction to determine the essential objective set [9]. Moreover, the FS-OPA preserves the original variable space, which favours non-expert human interpretability (relevant for some classes of real-world problems); it also has a relatively low-time complexity and has shown beneficial results when applied to small datasets [10,[16][17][18][19][20][21][22][23].…”
Section: Comparison Of Fs-opa With Nl-mvu-pca For Maops Data-driven S...mentioning
confidence: 99%
“…Naturally, pre-processing steps and some execution options may improve the DAMICORE performance. Its success in such a challenge has been checked for problems in a variety of fields, such as software-hardware co-design [23][24][25], compiler optimization [26], student profiling in e-learning environments [27,28], identification of phytopathology from sensor data [29], systematic literature review, identification of cross-cut concerns [30], and electrical distribution systems [31].…”
Section: Fs-opamentioning
confidence: 99%
“…The former works on the objective space for space reduction to determine the essential objective set [12]. FS-OPA also has other properties that are relevant for some classes of real-world problems: (i) it preserves the original variable space, which favours non-experts interpretability; (ii) it works with any data type (continuous, discrete, categorical-not only ordinal, but also nominal data, addressed by Bandaru et al [4]) and mixed types (proper for multiple heterogeneous databases with observed data); (iii) it has a relatively low time complexity; (iv) and, finally, it has generated applicable models when applied to learn from small datasets [17,[23][24][25][26][27][28][29][30][31].…”
Section: Comparison Of Fs-opa With Nl-mvu-pca For Maops Data-driven S...mentioning
confidence: 99%